Копредставление силовской p-подгруппы группы Sn - Скуратовский, Р.В. (Кибернетика и системный анализ, 2009)
Знайдено копредставлення силовської p-підгрупи симетричної групи у вигляді породжуючих і співвідношень. Досліджено силовську підгрупу групи S pk , тобто n-кратний вінцевий добуток регулярних циклічних груп простого порядка, яка ізоморфна групі автоморфізмів сферично-однорідного кореневого дерева. The ñîrepresentation of a Sylow p-subgroup of a symmetric group in the form of generating relations is investigated, and a Sylow subgroup of a group S pk , i.e., an n-fold intertwinement of regular cyclic groups of prime order, that is isomorphic to the group of automorphisms of a spherically homogeneous root tree is also studied.